The Case of California - Rickels, Laurence A. (punctum books, 2026)
Focusing on the changing image of the West Coast through such varied social and cultural artifacts as bodybuilding, group therapy, suicide cults, Marilyn Monroe, milk-carton images of missing children, orgies, Mickey Mouse, zombies, teenage slang, shock therapy, and surf music, The Case of California offers a dizzying psycho-history of the twentieth century as crystallized in the symbolic configuration and “case” of California, which case is articulated in relation to German modernism, National Socialism, and Freudian psychoanalysis. As Laurence Rickels writes, “on the personalizable level or label, California is a death cult; on the social, outward, happy-face level, it distributes pleasure via sadomasochism, the adolescent group, or friendship.” Ultimately, The Case of California excavates the places “California” occupies as concept or placeholder within Freudian psychoanalysis and such systems as the Frankfurt School, East Coast psychoanalysis, and deconstruction. To excavate the full range of “California,” one must apply pressure to a series of adjacent (and often equally marginal or missing) concepts, including group and adolescent psychology, female sexuality, the haunting of music and of mass media at large, the charge of child abuse, and a certain convergence of religious and hysterical conversion.